(untitled) (Bangladesh Journal of Agricultural Research, 2023)
The study was conducted to determine farmers’ attitude towards environment friendly vegetable cultivation and to explore the relationship of the selected characteristics with farmers’ attitude. The study also identified constraints faced by farmers in relation to environment friendly vegetable cultivation. Data were collected from 100 randomly selected respondents of three selected villages under Sadar upazila of Moulvibazar district using a pre-tested interview schedule during February-March 2018. Farmers’ attitude towards environment friendly vegetable cultivation (dependent variable) and was measured by 20 statements on 5-point scale and the eleven selected characteristics of the respondents. The highest proportion (40%) of the respondents had unfavorable attitude, 20% respondents had highly unfavorable attitude, 1% of them had neutral attitude, while 33% respondents had favorable attitude and 6% had highly favorable attitude towards environment friendly vegetable cultivation. The correlation analysis revealed that education, training received, time spent in vegetable cultivation, annual family income, annual income from vegetable cultivation, knowledge on environment friendly vegetable cultivation, organizational participation and credit received had significant positive relationship with the farmers’ attitude towards environment friendly vegetable cultivation. The majority (70%) of the farmers faced medium constraints while 3% faced high and 27% faced low constraints during environment friendly vegetable cultivation. Bangladesh J. Agril. Res. 46(2): 175-193, June 2021